2013
DOI: 10.3997/2214-4609.20131373
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of ERT-derived Temperature - Insights from Laboratory Measurements

Abstract: SUMMARYWe performed laboratory measurements on fully saturated sand samples in the context of deriving reliable temperature from time-lapse electrical resistivity tomography (ERT). The experiment consisted in monitoring an increase of temperature in sand samples with electrical resistivity measurements. We neglected the effect of surface conductivity since experiments showed two orders of magnitude between surface and fluid conductivities. We show that using simple linear relationship between fluid electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…imaging of heated water injection (Benderitter and Tabbagh, 1982;Hermans et al, 2015), monitoring of gas-phase formation due to heat storage (Lüders et al, 2016), geothermal exploration (Bruno et al, 2000;Garg et al, 2007), monitoring the performance of low enthalpy ground source energy systems (Fragkogiannis et al, 2008;Firmbach et al, 2013) and localizing the burning front of underground coal fires (Revil et al, 2013) to name but a few. Nevertheless, more examples are particularly necessary in real scale applications, since calibrated, robust and reliable correlations between electric resistivity and temperature are not available yet (Robert et al, 2013). Indeed, several uncertainties stand at field scale where different factors do affect the underground resistivity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…imaging of heated water injection (Benderitter and Tabbagh, 1982;Hermans et al, 2015), monitoring of gas-phase formation due to heat storage (Lüders et al, 2016), geothermal exploration (Bruno et al, 2000;Garg et al, 2007), monitoring the performance of low enthalpy ground source energy systems (Fragkogiannis et al, 2008;Firmbach et al, 2013) and localizing the burning front of underground coal fires (Revil et al, 2013) to name but a few. Nevertheless, more examples are particularly necessary in real scale applications, since calibrated, robust and reliable correlations between electric resistivity and temperature are not available yet (Robert et al, 2013). Indeed, several uncertainties stand at field scale where different factors do affect the underground resistivity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Their results show a very good agreement with direct temperature measurements in piezometers (maximum discrepancy of 20%, i.e., 1.5 • C). Robert et al [25] showed that for medium (T > 40 • C) and higher injection temperatures, ERT-derived temperature estimates do not follow a linear relationship anymore as shown by Hayley et al [18]. Indeed, at this temperature range, calcite, if close to saturation, starts to precipitate and the induced temperature change does not only increase the mobility of ions anymore but also modify the composition of dissolved minerals.…”
Section: Introductionmentioning
confidence: 96%
“…Some of these applications involved a quantitative evaluation of the thermal anomaly. Nevertheless, Robert et al (2013) under laboratory conditions highlighted problems of ERT-derived temperatures owing to temperature-related chemical reactions occurring within porous media, both on fluid and solid phases. They observed a divergence between the resistivity and temperature curves related to the increasing solubility of some minerals and the increasing fluid conductivity with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%